Preparation method and application of OP bidentate imine vanadium complex
By modifying the OP bidentate imine vanadium complex, a new catalyst was prepared, which solved the problem of low catalytic activity and poor high temperature resistance in the olefin copolymerization reaction, and achieved efficient and stable catalytic effect and long life.
Patent Information
- Application Number
- CN202410677963.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-05-29
AI Technical Summary
When existing catalysts catalyze olefin copolymerization reaction, the catalytic activity is low, the high temperature resistance is poor, the structure is difficult to regulate, and when catalyzing the copolymerization of ethylene and α-olefin, the comonomer insertion rate is low.
By reasonably modifying the structure of the OP bidentate imine vanadium complex, a new catalyst was prepared, which exhibits high catalytic activity, good thermal stability and long life in the copolymerization of ethylene with α-olefins and polar monomers.
The catalyst is used for low dosage, high activity, long life and good thermal stability, and the efficiency of copolymerization reaction and the quality of the product are improved, especially in high temperature conditions, which still maintains high catalytic activity.
Smart Images

Figure CN118598910B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of olefin polymerization catalysts, and in particular relates to a preparation method and application of an OP bidentate imine vanadium complex. Background Art
[0002] In the 1950s, Ziegler and Natta each found that transition metal complexes can catalyze olefin polymerization under mild conditions. In the more than 50 years since then, a large number of studies have emerged to develop highly active transition metal catalytic systems with high controllability of product structure. At the same time, the continuous renewal of polyolefin products has brought revolutionary changes to people's lives, and is increasingly widely used in industry, agriculture, national defense, transportation and people's daily lives. Therefore, organic ligands are effectively designed for molecular structure, and improving catalyst performance occupies a core position in the field of catalyst research and development. Scientists Nomura et al. reported aryl acyl monoimide vanadium catalysts (Macromolecules 2005, 38, 5905-5913), but the ability of the catalytic copolymerization of olefins is not strong, and the high temperature resistance is poor. Li Yuesheng et al. reported an OP bidentate vanadium (III) catalyst (Journal of Polymer Science, Part A: Polymer Chemistry 2012, 50, 4721-4731), which can catalyze the copolymerization of ethylene and ethylene with α-olefins. However, due to the paramagnetism of trivalent vanadium, it cannot be tested by nuclear magnetic resonance, which is not conducive to structural characterization. In addition, when it catalyzes the copolymerization of ethylene and α-olefins, the comonomer insertion rate in the obtained polymer is low.
[0003] Therefore, it is of great significance to change the structure of existing catalysts and design a catalyst that is simple to synthesize, convenient to purify, easy to characterize, easy to regulate the structure, has good high temperature tolerance, long life, low cost and excellent catalytic performance. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a preparation method and application of an OP bidentate imine vanadium complex. After reasonable modification, the prepared complex has the advantages of low use of co-catalyst, high catalytic activity, good thermal stability, long service life, etc.; at the same time, the catalyst can also efficiently catalyze the copolymerization reaction of ethylene with α-olefins and polar monomers.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] An OP bidentate imine vanadium complex has the following general structural formula:
[0007]
[0008] Wherein: R1 is an alkyl group containing 1 to 10 carbon atoms, an alkoxy group containing 1 to 10 carbon atoms, an aryl group, an aryl group containing a substituent, a carbazolyl group, an adamantyl group, a cumyl group, a diphenylmethyl group or a triphenylmethyl group;
[0009] R2 is an alkyl group containing 1 to 10 carbon atoms, an alkoxy group containing 1 to 10 carbon atoms, an aryl group or a cumyl group;
[0010] R3 is an alkyl group of 1 to 8 carbon atoms, a cycloalkyl group of 3 to 8 carbon atoms, or a substituted aryl group;
[0011] X is halogen, alkyl, silane or benzyl.
[0012] The present invention also provides a method for preparing an OP bidentate imine vanadium complex, comprising the following steps:
[0013] Under the catalysis of pyridinium p-toluenesulfonate, phenolic compounds and 3,4-dihydropyran undergo condensation reaction, and the obtained product is post-treated to obtain a white powder;
[0014] Under a nitrogen atmosphere, the white powder is added to THF, and the resulting solution is subjected to a metalation reaction with n-butyl lithium to generate a lithiated intermediate; the lithiated intermediate is reacted with phenylphosphine dichloride to form a phosphine compound;
[0015] Adding R3-MgX and water to the phosphine compound to quench the reaction, and obtaining an undeprotected ligand through post-treatment;
[0016] The undeprotected ligand is dissolved in CH2Cl2, water and concentrated hydrochloric acid are added to perform a hydrolysis reaction, and the ligand is obtained through post-treatment;
[0017] Under an inert atmosphere, adding a pentavalent transition vanadium compound of the fifth subgroup to dry benzene, stirring at room temperature, to obtain a solution;
[0018] The ligand is added to the solution in the form of powder, triethylamine is added, the mixture is stirred at room temperature, filtered, concentrated, and stirred after adding n-hexane. The precipitated solid is filtered and dried to obtain a vanadium complex.
[0019] Further, the molar ratio of the pyridinium p-toluenesulfonate, the phenolic compound and 3,4-dihydropyran is 5.6:112:168;
[0020] The molar ratio of the white powder, n-butyl lithium, diphenylphosphine chloride and R3-MgX is 34:37.4:39:41.
[0021] The invention also provides an application of an OP bidentate imine vanadium complex in catalyzing the copolymerization reaction of ethylene and alpha-olefin.
[0022] Furthermore, in the copolymerization reaction, the OP bidentate imine vanadium complex is used as the main catalyst, and the alkylaluminoxane, modified alkylaluminoxane, halogenated alkylaluminum or a mixture of alkylaluminum and a boron agent is used as the co-catalyst.
[0023] Further, the molar ratio of vanadium in the main catalyst to aluminum in the co-catalyst is 1:(5-10000);
[0024] The molar ratio of vanadium in the main catalyst to boron in the co-catalyst is 1:(0-2);
[0025] During the copolymerization reaction, the ethylene pressure is 0.1-10 MPa.
[0026] The present invention also provides an application of an OP bidentate imine vanadium complex in catalyzing the copolymerization reaction of ethylene and a polar monomer containing a hydroxyl group.
[0027] Furthermore, in the copolymerization reaction, the OP bidentate imine vanadium complex is used as the main catalyst, and the alkylaluminoxane, modified alkylaluminoxane, halogenated alkylaluminum or a mixture of alkylaluminum and a boron agent is used as the co-catalyst.
[0028] Further, the molar ratio of vanadium in the main catalyst to aluminum in the co-catalyst is 1:(5-10000);
[0029] The molar ratio of vanadium in the main catalyst to boron in the co-catalyst is 1:(0-2);
[0030] During the copolymerization reaction, the ethylene pressure is 0.1-10 MPa.
[0031] Compared with the prior art, the present invention has the following advantages and technical effects:
[0032] 1) The structure of the metal complex of the present invention is easy to modify and regulate;
[0033] 2) The synthesis route and purification method of the metal complex of the present invention are very simple, which is conducive to the realization of scale-up production;
[0034] 3) The present invention can more conveniently regulate the catalytic activity and copolymerization performance of the catalyst by directly changing the group R3 on the phosphorus atom connected to the metal center, thereby changing the steric hindrance and electron cloud density on the phosphorus, and then directly changing the steric hindrance and electron cloud density around the metal center;
[0035] 4) The catalyst of the present invention has high activity in catalyzing ethylene homopolymerization and can produce highly linear polyethylene;
[0036] 5) The catalyst of the present invention has good temperature resistance and can still maintain good catalytic activity under high temperature conditions;
[0037] 6) The metal center of the catalyst of the present invention is stable and the catalytic life is very long;
[0038] 7) The catalyst of the present invention catalyzes the copolymerization of ethylene and 1-hexene with high activity and a high comonomer insertion rate in the polymer;
[0039] 8) The catalyst of the present invention catalyzes the copolymerization reaction of ethylene and undecanol with high activity, and can obtain functionalized polyolefin products. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0041] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of the complex C1 provided in Example 2 of the present invention.
[0042] Figure 2 The carbon nuclear magnetic resonance spectrum of the copolymer of ethylene and 1-hexene provided in Application Example 2 of the present invention;
[0043] Figure 3 This is the hydrogen nuclear magnetic resonance spectrum of the copolymer of ethylene and undecenyl alcohol provided in Application Example 3 of the present invention. DETAILED DESCRIPTION
[0044] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0045] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0046] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0047] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0048] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0049] Unless otherwise specified, the "room temperature" in the present invention refers to 25°C.
[0050] The raw materials used in the invention are all purchased from the market.
[0051] The present invention provides an OP bidentate imine vanadium complex having the following general structural formula:
[0052]
[0053] Wherein: R1 is an alkyl group containing 1 to 10 carbon atoms, an alkoxy group containing 1 to 10 carbon atoms, an aryl group, an aryl group containing a substituent, a carbazolyl group, an adamantyl group, a cumyl group, a diphenylmethyl group or a triphenylmethyl group;
[0054] R2 is an alkyl group containing 1 to 10 carbon atoms, an alkoxy group containing 1 to 10 carbon atoms, an aryl group or a cumyl group;
[0055] R3 is an alkyl group of 1 to 8 carbon atoms, a cycloalkyl group of 3 to 8 carbon atoms, or a substituted aryl group;
[0056] X is halogen, alkyl, silane or benzyl.
[0057] In some preferred embodiments of the present invention, R1 is preferably phenyl, carbazolyl, adamantyl, cumyl or trityl; R2 is preferably tert-butyl (tBu), tert-octyl, methoxy or cumyl; R3 is preferably methyl, isopropyl, tert-butyl, cyclopentyl, cyclohexyl or p-fluorophenyl; X is preferably halogen or alkoxy.
[0058] The following 9 complexes (C1-C9) are preferred among the OP bidentate imine vanadium complexes, and their specific structural formulas are as follows:
[0059]
[0060]
[0061] The general structural formula of the ligand in the OP bidentate imine vanadium complex is as follows:
[0062] Wherein: R1 is an alkyl group containing 1 to 10 carbon atoms, an alkoxy group containing 1 to 10 carbon atoms, an aryl group, an aryl group containing a substituent, a carbazolyl group, an adamantyl group, a cumyl group, a diphenylmethyl group or a triphenylmethyl group;
[0063] R2 is an alkyl group containing 1 to 10 carbon atoms, an alkoxy group containing 1 to 10 carbon atoms, an aryl group or a cumyl group;
[0064] R3 is an alkyl group of 1 to 8 carbon atoms, a cycloalkyl group of 3 to 8 carbon atoms, or a substituted aryl group;
[0065] X is halogen, alkyl, silane or benzyl.
[0066] The ligands in the OP bidentate imine vanadium complex preferably have the following 9 structures (L1-L9):
[0067]
[0068] The preparation method of the OP bidentate imine vanadium complex comprises the following steps:
[0069] 1) A phenolic compound and 3,4-dihydropyran are used as raw materials, a condensation reaction is carried out under the catalysis of a catalyst, pyridinium p-toluenesulfonate, a saturated NaCl solution and a NaOH solution are added to the reactant for acid-base neutralization, an organic phase is separated and retained, the organic phase is washed with a saturated NaCl solution, dried, filtered, and rotary evaporated, and then anhydrous methanol is added thereto, stirred until a large amount of white precipitates are precipitated, filtered, and the filter cake is washed with anhydrous methanol to obtain a white solid, and the solvent is drained to obtain a white powder;
[0070] The phenolic compound is a known raw material in the prior art and can be directly purchased or synthesized using conventional methods. The preparation method of the compound is not used as a consideration criterion for examining the creativity of the present invention, and it only needs to be able to be successfully prepared.
[0071] 2) under a nitrogen atmosphere, adding the white powder into tetrahydrofuran (THF), and reacting the obtained solution with n-butyl lithium to form a lithiated intermediate; the lithiated intermediate reacts with phenylphosphine dichloride to form a phosphine compound;
[0072] Adding R3-MgX and water to the phosphine compound to quench the reaction, and obtaining an undeprotected ligand through post-treatment;
[0073] CH2Cl2 was added to dissolve, saturated NaCl solution was added thereto, the organic phase was separated and retained, the organic phase was washed with saturated NaCl solution, dried, filtered, the filtrate was concentrated, anhydrous methanol was then added to the reaction bottle, ultrasonic vibration was performed, white powder was precipitated, and filtered to obtain the compound;
[0074] 3) dissolving the compound in CH2Cl2, adding water and concentrated hydrochloric acid to carry out hydrolysis reaction, adding saturated NaCl solution after the reaction is complete, then dropping NaHCO3 solution to adjust pH=7, separating and retaining the organic phase, washing the organic phase with saturated NaCl solution, drying, filtering, rotary evaporation, and purifying the crude product by column chromatography (ethyl acetate: petroleum ether=1:50) to obtain the ligand;
[0075] 4) under an inert atmosphere, adding a pentavalent transition vanadium compound of the fifth subgroup to dry benzene, stirring at room temperature to obtain a solution; adding the ligand obtained in step 3) to the solution in the form of powder, adding triethylamine, stirring at room temperature, filtering, concentrating, adding n-hexane and stirring, filtering and draining the precipitated solid to obtain a vanadium complex.
[0076] In some preferred embodiments of the present invention, the molar ratio of the pyridinium p-toluenesulfonate, the phenolic compound and 3,4-dihydropyran is 5.6:112:168; the molar ratio of the white powder, n-butyl lithium, diphenylphosphine chloride and R3-MgX is 34:37.4:39:41. In the R3-MgX, X is Cl or Br, and R3 is an alkyl group of 1 to 8 carbon atoms, a cycloalkyl group of 3 to 8 carbon atoms or a substituted aryl group.
[0077] The use of the OP bidentate imine vanadium complex in catalyzing the copolymerization of ethylene and α-olefin. In the copolymerization, the OP bidentate imine vanadium complex is used as the main catalyst, and alkylaluminoxane, modified alkylaluminoxane, halogenated alkylaluminum or a mixture of alkylaluminum and a boron agent is used as a co-catalyst, preferably diethylaluminum chloride. The molar ratio of vanadium in the main catalyst to aluminum in the co-catalyst is 1: (5-10000), preferably 1: (100-5000); the molar ratio of vanadium in the main catalyst to boron in the co-catalyst is 1: (0-2), that is, the boron agent may not be added; in the copolymerization, the pressure of ethylene is 0.1-10MPa, preferably 0.1-1.0MPa.
[0078] The use of the OP bidentate imine vanadium complex in catalyzing the copolymerization of ethylene and a polar monomer containing a hydroxyl group. In the copolymerization reaction, the OP bidentate imine vanadium complex is used as the main catalyst, and alkylaluminoxane, modified alkylaluminoxane (purchased from Nouryon), halogenated alkylaluminum or a mixture of alkylaluminum and a boron agent is used as a co-catalyst, preferably diethylaluminum chloride. The molar ratio of vanadium in the main catalyst to aluminum in the co-catalyst is 1: (5-10000), preferably 1: (100-5000); the molar ratio of vanadium in the main catalyst to boron in the co-catalyst is 1: (0-2); in the copolymerization reaction, the pressure of ethylene is 0.1-10MPa, preferably 0.1-1.0MPa.
[0079] In the application process of the OP bidentate fifth subgroup pentavalent metal complex in catalyzing the copolymerization of ethylene and hydroxyl-containing polar monomers, the hydroxyl-containing polar monomers need to be pretreated with part of the co-catalyst in advance, and the pretreated product is then reacted with the main catalyst and the remaining co-catalyst. The molar ratio of the hydroxyl-containing polar monomer to part of the co-catalyst is (1.0-1.2):1, preferably 1:1. In the embodiment, the amount of the co-catalyst used for pre-treating the polar monomer is combined with the co-catalyst that plays a catalytic role.
[0080] The technical solution of the present invention is further described by way of examples. In the following examples, the preferred ligands L1-L9 are used as examples for experiments, and the corresponding metal complexes are C1-C9.
[0081] Example 1
[0082] A ligand (L1-L9) of an OP bidentate imine vanadium complex is prepared in the following manner:
[0083]
[0084] (1) Preparation of compound (B): The corresponding phenolic compound 2-R1-4-R2-phenol (112 mmol, eq=1.0), pyridinium p-toluenesulfonate (PPTS, 5.6 mmol, eq=0.05), and CH2Cl2 (300 mL) were added to a 500 mL Schlenck bottle in sequence. The reaction bottle was placed in an ice-water bath and stirred. After 10 minutes, 3,4-dihydropyran (DHP, 168 mmol, eq=1.5) was added dropwise. After about 10 minutes, the addition was completed and the ice-water bath was removed. , continue the reaction for 3 hours, add saturated NaCl solution (100 mL) and NaOH solution (50 mL, 1 mol / L) to the reaction flask in turn, stir for 10 minutes, separate the liquid and retain the organic phase, wash the organic phase with saturated NaCl solution three times, then add anhydrous magnesium sulfate to dry, filter, and remove most of the solvent by rotary evaporation, add anhydrous methanol (200 mL) to it, stir rapidly for 20 minutes, precipitate a large amount of white precipitate, filter, and wash the filter cake with anhydrous methanol twice to obtain a white solid, and drain the solvent to obtain a white powder (B).
[0085] (2) Preparation of compound (C): Compound (B) (34 mmol, eq=1.00) was added to a 200 mL Schlenck bottle, replaced with N2 atmosphere, and dry THF (120 mL) was introduced thereto for dissolution. The reaction bottle was placed in an ice-water bath and stirred. After 10 min, n-butyl lithium (37.4 mmol, eq=1.10) was added dropwise thereto. The ice-water bath was removed, and the temperature was raised to room temperature and the reaction was continued for 5 h to obtain a reaction solution.
[0086] Under N2 atmosphere, PhPCl2 (39 mmol, eq=1.15) and dry THF (150 mL) were added to another 500 mL Schlenck bottle in sequence, stirring was started and the system was cooled to -78°C, and then the reaction solution prepared in the previous article was slowly dripped into the system using a double-headed solvent transfer needle. After the dripping was completed, the temperature was slowly raised to room temperature for reaction for 3 h; then the system was cooled to 0°C, R3-MgX (41 mmol, eq=1.20, X=Cl or Br) was slowly dripped into it, the low temperature was removed, and the temperature was raised to 50°C to continue the reaction for 12 h;
[0087] 1 mL of water was added to the reaction flask to quench the reaction, and then the THF solvent was removed by rotary evaporation. CH2Cl2 (150 mL) was added to dissolve, and saturated NaCl solution (100 mL) was added thereto. The organic phase was separated and retained. The organic phase was washed with saturated NaCl solution for 3 times, and then anhydrous magnesium sulfate was added thereto to dry, filtered, and the filtrate was concentrated to 20 mL. Then anhydrous methanol (150 mL) was added to the reaction flask, and ultrasonic vibration was performed for 10 min to precipitate a white powder, which was filtered to obtain compound (C).
[0088] (3) Preparation of ligand (L): Compound (C) was dissolved in CH2Cl2 (150 mL), and then water (5 mL) and concentrated hydrochloric acid (2 mL) were added thereto. The reaction was stirred at room temperature and followed by TLC plate. After the reaction was complete, saturated NaCl solution (100 mL) was added thereto, and then NaHCO3 solution (2 mol / L) was added dropwise thereto to adjust the pH to 7. The organic phase was separated and retained. The organic phase was washed three times with saturated NaCl solution, and then anhydrous sodium sulfate was added thereto for drying. The mixture was filtered and the solvent was removed by rotary evaporation. The crude product was purified by column chromatography (ethyl acetate: petroleum ether = 1:50) to obtain ligand (L).
[0089] The phenolic compound (A) 2-R1-4-R2-phenol is 2,4-dicumylphenol; 2-cumyl-4-methoxyphenol; 2-cumyl-4-tert-butylphenol; R3-MgX is methylmagnesium bromide, isopropylmagnesium chloride, tert-butylmagnesium chloride, cyclopentylmagnesium bromide, cyclohexylmagnesium bromide, 4-fluorophenylmagnesium bromide, and they are combined to obtain ligands L1-L9.
[0090] The synthesis and purification process of ligands L1-L9 is completely consistent with the methods described in (1), (2) and (3) above. Compounds (B) and (C) containing different substituent structures are both obtained by recrystallization from methanol.
[0091] The experimental results of ligands L1-L9 are as follows:
[0092] L1: white powdery solid, yield: 42.6%. 1H NMR (400MHz, CDCl3) δ7.31 (d, J=2.2Hz, 1H, Ar-H), 7.27-7.13 (m, 14H, Ar-H), 6.94 (dd, J=5.3, 2.2Hz, 1H, Ar-H), 5.49 (d, J=4.0Hz,1H,Ar-H),1.64(d,J=2.9Hz,6H,Cumyl-CH3),1.61(d,J=6.5Hz,6H,Cumyl-CH3),1.48(d,J=2.7Hz,3H,P-CH3); 31 P NMR(162MHz, CDCl3)δ-44.99(s);
[0093] L2: colorless oily liquid, yield: 45.5%. 1 H NMR(400MHz, CDCl3)δ7.31(ddd,J=8.4,5.5,2.0Hz,3H,Ar-H),7.26-7.10(m,12H,A r-H),7.03(dd,J=4.2,2.3Hz,1H,Ar-H),6.13(d,J=7.5Hz,1H,Ar-H),2.24(dp,J=1 3.8,6.9Hz,1H,P-CH-),1.66(d,J=1.8Hz,6H,Cumyl-CH3),1.62(d,J=2.6Hz,6H,Cu myl-CH3),0.99(dd,J=16.9,6.9Hz,3H,-CH3),0.88(dd,J=15.5,6.9Hz,3H,-CH3); 31 P NMR(162MHz, CDCl3)δ-24.74(s);
[0094] L3: white powdery solid, yield: 54.8%. 1 H NMR (400MHz, CDCl3) δ7.42 (d, J=2.3Hz, 1H, Ar-H), 7.37 (td, J=7.5, 1.8Hz, 2H, Ar-H), 7.29-7.26 (m, 3H, Ar-H), 7.24-7.09 (m, 10H, Ar-H) ,6.91(d,J=10.2Hz,1H,Ar-H),1.69(d,J=3.5Hz,6H,Cumyl-CH3),1.66(d,J=10.6Hz,6H,Cumyl-CH3),0.99(d,J=13.5Hz,9H,-C(CH3)3); 31 PNMR(162MHz, CDCl3)δ-17.30(s);
[0095] L4: white powdery solid, yield: 45.8%.1 H NMR (400MHz, CDCl3) δ7.34-7.27(m,3H,Ar-H),7.25-7.09(m,12H,Ar-H),7.03(d,J=2.0Hz,1H,Ar-H),5 .90(d,J=5.7Hz,1H,Ar-H),2.37(dd,J=15.8,7.9Hz,1H,Cyclopentyl-H),1.79-1.39(m,20H,Cumyl-CH3 andCyclopentyl-H); 31 P NMR(162MHz, CDCl3)δ-27.20(s);
[0096] L5: white powdery solid, yield: 49.6%. 1 H NMR(400MHz, CDCl3) δ7.36(d,J=1.3Hz,1H,Ar-H),7.29(d,J=4.8Hz,2H,Ar-H),7.26-7.11(m,12H,Ar-H),6.99(s ,1H,Ar-H),6.10(d,J=7.4Hz,1H,Ar-H),2.03-1.90(m,1H,Cyclohexyl-H),1.65(d,J=17.5Hz,16H,Cumyl-CH3and Cyclohexyl-H), 1.43 (d, J=10.8Hz, 1H, Cyclohexyl-H), 1.12 (dd, J=16.5, 7.7Hz, 5H, Cyclohexyl-H); 31 P NMR(162MHz, CDCl3)δ-29.96(s);
[0097] L6: white powdery solid, yield: 59.3%. 1 H NMR (400MHz, CDCl3) δ7.35(d,J=2.1Hz,1H,Ar-H),7.29(d,J=8.0Hz,2H,Ar-H),7.21(dd,J=15.2,7.9Hz,6H,Ar-H),7.17-7.08(m,7H,Ar -H),6.92(t,J=8.5Hz,2H,Ar-H),6.42(dd,J=5.2,2.2Hz,1H,Ar-H),4.99(s,1H,-OH),1.61(s,6H,Cumyl-CH3),1.54(s,6H,Cumyl-CH3); 31 P NMR (162MHz, CDCl3) δ-20.67 (d, J=4.3Hz);
[0098] L7: colorless oily liquid, yield: 64.8%. 1 H NMR (400MHz, CDCl3) δ7.44 (td, J=7.4, 2.8Hz, 2H, Ar-H), 7.28 (d, J=4.1Hz, 3H, Ar-H), 7.24-7.19 (m ,3H,Ar-H),7.14(dt,J=8.5,3.1Hz,1H,Ar-H),7.05(d,J=2.8Hz,1H,Ar-H),6.70(t,J=3.4Hz,1H,A r-H),5.77(d,J=7.0Hz,1H,Ar-H),3.72(s,3H-OCH3),2.39(m,J=13.9,7.0Hz,1H,P-CH-),1.67(d, J=1.8Hz,6H,Cumyl-CH3),1.06(dd,J=16.8,6.9Hz,3H,-CH3),0.97(dd,J=15.6,6.9Hz,3H,-CH3); 31 PNMR(162MHz,CDCl3)δ-20.67(d,J=4.3Hz);
[0099] L8: colorless oily liquid, yield: 59.5%. 1 H NMR(400MHz, CDCl3) δ7.52(t,J=6.3Hz,2H,Ar-H),7.30(d,J=5.4Hz,3H,Ar-H),7.24-7.19(m,4H,Ar-H),7.16-7.10(m,2H,Ar-H),6.8 7(s,1H,-OH),6.52(d,J=9.6Hz,1H,Ar-H),3.75(s,3H,-OCH3),1.69(d,J=4.5Hz,6H,Cumyl-CH3),1.14(d,J=13.5Hz,9H,-C(CH3)3); 31 P NMR(162MHz, CDCl3)δ-13.77(s);
[0100] L9: white powdery solid, yield: 38.7%. 1H NMR (400MHz, CDCl3) δ7.46 (d, J=2.1Hz, 1H, Ar-H), 7.38 (td, J=7.2, 2.8Hz, 2H, Ar-H), 7.27 (s, 1H, Ar-H), 7.25 -7.19(m,6H,Ar-H),7.17-7.12(m,1H,Ar-H),5.81(d,J=6.0Hz,1H,Ar-H),2.56(dd,J=16.5,8.2Hz,1H,Cyclo pentyl-H),1.84(s,1H,Cyclopentyl-H),1.76-1.69(m,1H,Cyclopentyl-H),1.68(d,J=2.9Hz,6H,Cumyl-CH 3),1.65-1.45(m,5H,Cyclopentyl-H),1.37(dd,J=14.7,7.5Hz,1H,Cyclopentyl-H),1.30(s,9H,-C(CH3)3); 31 PNMR(162MHz,CDCl3)δ-25.44(s).
[0101] Example 2
[0102] An OP bidentate imine vanadium complex (C1-C9) is prepared in the following manner:
[0103]
[0104] Under an inert gas environment, V(N-2,6-Me2C6H3)Cl30.5000g (1.81mmol, eq=1.02) and 30mL of dry benzene were added to a 100mL Schlenk bottle in sequence, and the solid was dissolved by stirring at room temperature for 10min. Then, the ligands L1-L9 (1.77mmol, eq=1.00) powders were directly added to the above system, and the bottle wall was rinsed with 20mL of anhydrous benzene. After stirring for 10min, 0.30mL of triethylamine (2.13mmol, eq=1.20) was added thereto, and the reaction was stirred at room temperature overnight. The triethylamine hydrochloride was filtered out, and the filtrate was concentrated to 15mL, and then 30mL of n-hexane was added thereto, and the solid was rapidly stirred for 20min. A large amount of solid was precipitated, and the vanadium complex was obtained by filtering and drying.
[0105] The experimental results of vanadium complexes C1-C9 are as follows:
[0106] C1: gray-green powder, yield: 75.7%. 11H NMR (400 MHz, C6D6) δ 7.57 - 7.48 (m, 3H, Ar - H), 7.26 (t, J = 7.7 Hz, 2H, Ar - H), 7.11 (d, J = 4.5 Hz, 4H, Ar - H), 7.02 (dd, J = 12.0, 6.7 Hz, 4H, Ar - H), 6.84 (dd, J = 7.4, 1.8 Hz, 1H, Ar - H), 6.76 - 6.69 (m, 1H, Ar - H), 6.65 (t, J = 6.9 Hz, 2H, Ar - H), 6.38 - 6.31 (m, 1H, Ar - H), 6.27 (d, J = 7.1 Hz, 2H, Ar - H), 2.02 (s, 6H, Ar - CH3), 1.93 (s, 3H, Cumyl - CH3), 1.86 (s, 3H, Cumyl - CH3), 1.48 (s, 6H, Cumyl - CH3), 1.29 (d, J = 12.2 Hz, 3H, P - CH3); See Figure 1 ;
[0107] C2: Yellow solid, yield: 81.5%. 1 1H NMR (400 MHz, C6D6) δ 7.60 (d, J = 1.9 Hz, 1H, Ar - H), 7.51 (d, J = 7.4 Hz, 2H, Ar - H), 7.29 (t, J = 7.8 Hz, 2H, Ar - H), 7.12 (m, 2H, Ar - H), 7.09 - 7.05 (m, 5H, Ar - H), 6.98 (dt, J = 5.8, 3.7 Hz, 1H, Ar - H), 6.82 (dd, J = 6.3, 2.1 Hz, 1H, Ar - H), 6.76 (dd, J = 8.4, 6.6 Hz, 1H, Ar - H), 6.66 (td, J = 7.6, 2.1 Hz, 2H, Ar - H), 6.34 (t, J = 7.3 Hz, 1H, Ar - H), 6.24 (d, J = 7.6 Hz, 2H, Ar - H), 2.48 (m, J = 13.8, 6.8 Hz, 1H, P - CH -), 1.93 (s, 6H, Ar - CH3), 1.90 (s, 3H, Cumyl - CH3), 1.83 (s, 3H, Cumyl - CH3), 1.49 (d, J = 1.9 Hz, 6H, Cumyl - CH3), 0.73 (dd, J = 20.3, 6.9 Hz, 3H, - CH3), 0.59 (dd, J = 11.5, 7.0 Hz, 3H, - CH3);
[0108] C3: Green crystalline solid, yield: 62.1%. 11H NMR (400 MHz, C6D6) δ 7.64 (s, 1H, Ar-H), 7.56 (t, J = 8.6 Hz, 2H, Ar-H), 7.49 (d, J = 7.6 Hz, 2H, Ar-H), 7.26 (t, J = 7.7 Hz, 2H, Ar-H), 7.14 - 6.99 (m, 7H, Ar-H), 6.66 (dt, J = 15.7, 7.9 Hz, 3H, Ar-H), 6.30 - 6.17 (m, 3H, Ar-H), 2.05 (s, 6H, Ar-CH3), 1.92 (s, 3H, Cumyl-CH3), 1.82 (s, 3H, Cumyl-CH3), 1.58 (d, J = 7.6 Hz, 6H, Cumyl-CH3), 0.94 (d, J = 14.7 Hz, 9H, -C(CH3)3);
[0109] C4: Yellowish green solid, yield: 65.4%. 1 1H NMR (400 MHz, C6D6) δ 7.60 (d, J = 1.9 Hz, 1H, Ar-H), 7.49 (d, J = 7.4 Hz, 2H, Ar-H), 7.30 (t, J = 7.7 Hz, 2H, Ar-H), 7.16 (dd, J = 11.4, 6.4 Hz, 2H, Ar-H), 7.11 - 7.02 (m, 5H, Ar-H), 7.00 - 6.93 (m, 1H, Ar-H), 6.86 - 6.77 (m, 2H, Ar-H), 6.70 (td, J = 7.7, 2.2 Hz, 2H, Ar-H), 6.38 (t, J = 7.5 Hz, 1H, Ar-H), 6.28 (d, J = 7.6 Hz, 2H, Ar-H), 2.74 (m, J = 8.4, 3.2 Hz, 1H, P-CH-), 1.96 (s, 6H, Ar-CH3), 1.93 (s, 3H, Cumyl-CH3), 1.81 (s, 3H, Cumyl-CH3), 1.47 (d, J = 4.9 Hz, 6H, Cumyl-CH3), 1.43 - 1.30 (m, 1H, Cyclopentyl-H), 1.27 - 0.79 (m, 7H, Cyclopentyl-H);
[0110] C5: Brownish yellow solid, yield: 77.2%. 1H NMR (400MHz, CDCl3) δ7.59(d,J=1.8Hz,1H,Ar-H),7.36(s,1H,Ar-H),7.31-7.22(m,5H,Ar-H),7.22-7.08(m,7H,Ar-H),7.00(td,J=7.8,2 .3Hz,2H,Ar-H),6.74(dd,J=6.6,2.0Hz,1H,Ar-H),6.69(t,J=7.6Hz,1H,Ar-H),6.55(d,J=7.6Hz,2H,Ar-H),2.47-2.35(m,1H,Cyclohexyl -H),1.84(s,6H,Ar-CH3),1.81(s,3H,Cumyl-CH3),1.75(s,3H,Cumyl-CH3),1.70(d,J=5.2Hz,6H,Cumyl-CH3),1.66-1.35(m,6H,Cyclohex yl-H), 1.15 (dd, J=26.2, 13.2Hz, 2H, Cyclohexyl-H), 0.74 (q, J=12.7Hz, 1H, Cyclohexyl-H), 0.34 (dd, J=18.1, 9.1Hz, 1H, Cyclohexyl-H);
[0111] C6: gray-green powder, yield: 72.6%. 1 H NMR (400MHz, C6D6) δ7.49 (d, J=6.1Hz, 3H, Ar-H), 7.35 (dd, J=10.6, 8.0Hz, 2H, Ar- H),7.23(dd,J=14.7,6.9Hz,4H,Ar-H),7.09-6.92(m,7H,Ar-H),6.85-6.79(m,1H ,Ar-H),6.75(t,J=6.6Hz,2H,Ar-H),6.43-6.32(m,3H,Ar-H),6.27(d,J=7.5Hz,2 H,Ar-H),2.04(s,6H,,Ar-CH3),1.90(s,6H,Cumyl-CH3),1.44(s,6H,Cumyl-CH3);
[0112] C7: grass green crystalline solid, yield: 79.8%. 11H NMR (400 MHz, C6D6) δ 7.48 (d, J = 7.6 Hz, 2H, Ar-H), 7.32 - 7.25 (m, 3H, Ar-H), 7.23 - 7.17 (m, 2H, Ar-H), 7.07 (t, J = 7.3 Hz, 1H, Ar-H), 6.82 (t, J = 7.2 Hz, 1H, Ar-H), 6.71 (d, J = 7.4 Hz, 2H, Ar-H), 6.41 - 6.32 (m, 2H, Ar-H), 6.25 (d, J = 7.5 Hz, 2H, Ar-H), 3.18 (s, 3H, -OCH3), 2.62 - 2.50 (m, 1H, P-CH-), 1.92 (s, 6H, Ar-CH3), 1.87 (s, 3H, Cumyl-CH3), 1.78 (s, 3H, Cumyl-CH3), 0.75 - 0.64 (m, 6H, -CH3);
[0113] C8: Yellow solid, yield: 74.2%. 1 1H NMR (400 MHz, C6D6) δ 7.76 - 7.69 (m, 2H, Ar-H), 7.46 (d, J = 7.5 Hz, 2H, Ar-H), 7.25 (t, J = 7.7 Hz, 3H, Ar-H), 7.04 (t, J = 7.3 Hz, 1H, Ar-H), 6.83 (dd, J = 5.3, 2.8 Hz, 1H, Ar-H), 6.77 - 6.65 (m, 3H, Ar-H), 6.30 - 6.24 (m, 1H, Ar-H), 6.19 (d, J = 7.5 Hz, 2H, Ar-H), 3.30 (s, 3H, -OCH3), 2.06 (s, 6H, Ar-CH3), 1.89 (s, 3H, Cumyl-CH3), 1.75 (s, 3H, Cumyl-CH3), 0.98 (d, J = 14.7 Hz, 9H, -C(CH3)3);
[0114] C9: Brown solid, yield: 69.0%. 1H NMR (400MHz, C6D6) δ7.65 (s, 1H, Ar-H), 7.51 (d, J = 7.8Hz, 2H, Ar-H), 7.29 (dd, J=16.0,8.1Hz,4H,Ar-H),7.08(t,J=7.3Hz,1H,Ar-H),7.04(d,J=4.8Hz,1H,Ar -H),6.87(t,J=7.3Hz,1H,Ar-H),6.77(t,J=6.7Hz,2H,Ar-H),6.37(t,J=7.4Hz,1H,Ar-H),6.26(d,J=7.5Hz,2H,Ar-H),2.88-2.76(m,1H,Cyclopentyl-H),1 .97(s,3H,Cumyl-CH3),1.95(s,6H,Ar-CH3),1.88(s,3H,Cumyl-CH3),1.85-1.78(m,1H,Cyclopentyl-H),1.52(td,J=13.5,7.5Hz,1H,Cyclopentyl-H),1.3 7(dt,J=14.2,8.0Hz,1H,Cyclopentyl-H),1.20-1.13(m,2H,Cyclopentyl-H),1.11(s,9H,-C(CH3)3),0.99(ddd,J=19.8,15.2,7.6Hz,3H,Cyclopentyl-H).
[0115] Application Example 1
[0116] Example 2: The obtained C1-C9 catalyzed ethylene high pressure polymerization: The polymerization reaction was carried out in a 250 mL stainless steel autoclave. The autoclave equipped with mechanical stirring was heated to 200°C, vacuumed for 1 hour, the system was adjusted to the temperature conditions required for polymerization, 0.1 MPa of ethylene gas was charged, 200 mL of toluene solution containing a co-catalyst and a reactivating agent (ethyl trichloroacetate) was added to the autoclave, and the temperature was kept constant for a period of time (see Table 1), and a certain pressure of ethylene gas was introduced. Wait for 10 minutes to allow ethylene to reach a dissolution equilibrium, and then the main catalyst was added and stirred for a period of time. After the polymerization reaction was completed, the residual ethylene gas was released, the autoclave was opened, and the obtained polymerization reaction mixture was poured into a mixed solution of 3M hydrochloric acid and ethanol in a volume ratio of 1:1, stirred for 15 minutes, filtered, and the polyethylene product was dried in a vacuum oven. Weigh its mass, measure its molecular weight, molecular weight distribution and melting point.
[0117] a Polymerization conditions: The amount of the main catalyst C1-C9 was 0.2 μmol, the co-catalyst was Et2AlCl: 2 mmol, the polymerization pressure was 0.50 MPa, and the polymerization time was 10 min. The results are shown in Table 1.
[0118] Table 1 Data of high pressure homopolymerization of ethylene catalyzed by selected main catalysts a
[0119]
[0120] Note: c Mw (molecular weight), c PDI (molecular weight distribution) is measured by high temperature GPC; d Tm (melting point) was measured by DSC; f 12: Polymerization time is 30min; g 13: The polymerization time is 60 minutes.
[0121] Application Example 2
[0122] Example 2 The prepared C1-C9 catalyzes the copolymerization of ethylene and α-olefins: The polymerization reaction is carried out in a 250mL stainless steel autoclave. The polymerization autoclave equipped with mechanical stirring is heated to 200°C, vacuumed for 1h, the system is adjusted to the temperature conditions required for polymerization, 0.1MPa of ethylene gas is charged, and a toluene solution containing a certain amount of diethylaluminum chloride, a reactivating agent (ethyl trichloroacetate) and a certain concentration of α-olefin (1-hexene) is added to the polymerization autoclave (the final total volume of the solution is 200mL), and the temperature is kept for a period of time until the temperature is constant, 0.5MPa of ethylene gas is passed, and 10min is waited for ethylene to reach a dissolution equilibrium, and then the main catalyst is added and stirred for a period of time. After the polymerization reaction is completed, the residual ethylene gas is released, the reactor is opened, and the obtained polymerization reaction mixture is poured into a mixed solution of 3M hydrochloric acid and ethanol in a volume ratio of 1:1, stirred for 15min, filtered, and the polymer product is dried in a vacuum oven. Weigh its mass, measure its molecular weight and molecular weight distribution, and measure the comonomer insertion rate by nuclear magnetic carbon spectrum.
[0123] a Polymerization conditions: the amount of main catalyst C1-C9 is 1 μmol, the co-catalyst is Et2AlCl: 2 mmol, the polymerization temperature is 50°C, the polymerization pressure is 0.50 MPa, and the polymerization time is 10 min. The results are shown in Table 2. The nuclear magnetic resonance carbon spectrum of the copolymer of ethylene and 1-hexene under the catalytic action of catalyst C7 (C7 of sequence number 10 in Table 2) is shown in Figure 2 .
[0124] Table 2 Data of copolymerization of ethylene and 1-hexene catalyzed by selected main catalysts a
[0125]
[0126]
[0127] Note:c Mw (molecular weight), c PDI (molecular weight distribution) is measured by high temperature GPC; d The 1-hexene insertion rate is given by 13 Measured by CNMR.
[0128] Application Example 3
[0129] Example 2 The prepared C1-C2, C7-C8 catalytic ethylene and polar monomer copolymerization: The polymerization reaction was carried out in a 250mL stainless steel autoclave, the polymerization kettle equipped with mechanical stirring was heated to 200°C, vacuumed for 1h, the system was adjusted to the required temperature conditions for polymerization, 0.1MPa of ethylene gas was charged, a toluene solution containing a certain amount of diethylaluminum chloride, a reactivator (ethyl trichloroacetate) and a certain concentration of polar monomer (undecylenol) pretreated with diethylaluminum chloride was added to the polymerization kettle (the final total volume of the solution was 60mL), the temperature was kept for a period of time until the temperature was constant, 0.5MPa of ethylene gas was passed, and ethylene was allowed to reach a dissolution equilibrium for 10min, then the main catalyst was added and stirred for a period of time. After the polymerization reaction was completed, the residual ethylene gas was released, the reactor was opened, and the obtained polymerization reaction mixture was poured into a mixed solution of 3M hydrochloric acid and ethanol in a volume ratio of 1:1, stirred for 15min and then filtered, and the polymer product was dried in a vacuum oven. Weigh its mass, measure its molecular weight and molecular weight distribution, and measure the comonomer insertion rate by nuclear magnetic hydrogen spectrum.
[0130] The molar ratio of diethylaluminum chloride used for pretreating polar monomers to polar monomers is 1:1, and the pretreatment time is 20 min. The amount of co-catalyst added in Table 3 is the total amount of diethylaluminum chloride added to the reaction system, excluding the remaining amount used for pretreating polar monomers to play a co-catalyst role.
[0131] a Polymerization conditions: the amount of the main catalyst is 1 μmol, the co-catalyst is Et2AlCl, the amount added is shown in Table 1, the polymerization temperature is 50°C, the reactivating agent is ethyl trichloroacetate: 0.3 mmol, the polymerization pressure is 0.50 MPa, and the polymerization time is 10 min. The results are shown in Table 3. The nuclear magnetic resonance hydrogen spectrum of the copolymer of ethylene and undecene alcohol under the catalytic action of catalyst C1 (C1 of sequence number 1 in Table 3) is shown in Figure 3 .
[0132] Table 3 Data of copolymerization of ethylene and undecenol catalyzed by selected main catalysts a
[0133]
[0134] Note: c Mw (molecular weight), c PDI (molecular weight distribution) is measured by high temperature GPC;d The insertion rate of undecenol is given by 1 Measured by HNMR.
[0135] The experimental results show that the activity of the novel OP bidentate imine vanadium complex catalyzing ethylene homopolymerization (0.5 MPa) can reach up to 195.63×10 6 g / (molV·h), and it still has catalytic activity when the reaction is carried out for 60 min; when the concentration of 1-hexene is 2 mol / L, the activity of catalyzing the copolymerization of ethylene and 1-hexene can reach 7.94×10 6 g / (molV·h), and the molecular weight of the obtained polymer was as high as 22.6×10 4 g / mol, the highest molar insertion rate of 1-hexene was 30.2%; when the concentration of undecenol was 0.5 mol / L, the activity of catalyzing the copolymerization of ethylene and undecenol could reach 8.03×10 6 g / (molV·h), and the molecular weight of the obtained polymer was as high as 29.2×10 4 g / mol, and the highest molar insertion rate of undecenol was 6.1%.
[0136] It can be seen from the above embodiments that the present invention provides a novel OP bidentate imine vanadium complex, which has high catalytic activity, long service life, and good temperature resistance when catalyzing ethylene polymerization, and can still maintain high catalytic activity at 100°C; it catalyzes the copolymerization of ethylene and 1-hexene, showing ultra-high activity, and the molecular weight and insertion rate of the obtained polymer are relatively high; it catalyzes the copolymerization of ethylene and undecenol, has high catalytic activity, and the molecular weight and comonomer content are also high, and a functionalized polymer product is obtained.
[0137] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. An OP bidentate imine vanadium complex, characterized in that: It has the following general structural formula: Wherein: R1 is cumyl; R2 is tert-butyl, methoxy or cumyl; R3 is methyl, isopropyl, tert-butyl, cyclopentyl, cyclohexyl or p-fluorophenyl; X is chlorine.
2. A method for preparing the OP bidentate imine vanadium complex as claimed in claim 1, characterized in that: The following steps are involved: Under the catalysis of pyridinium p-toluenesulfonate, phenolic compounds and 3,4-dihydropyran undergo condensation reaction, and the obtained product is post-treated to obtain a white powder; Under a nitrogen atmosphere, the white powder is added to THF, and the resulting solution is subjected to a metalation reaction with n-butyl lithium to generate a lithiated intermediate; the lithiated intermediate is reacted with phenylphosphine dichloride to form a phosphine compound; Adding R3-MgX and water to the phosphine compound to quench the reaction, and obtaining an undeprotected ligand through post-treatment; The undeprotected ligand is dissolved in CH2Cl2, water and concentrated hydrochloric acid are added to perform a hydrolysis reaction, and the ligand is obtained through post-treatment; Under an inert atmosphere, adding a pentavalent transition vanadium compound of the fifth subgroup to dry benzene, stirring at room temperature, to obtain a solution; The ligand is added to the solution in the form of powder, triethylamine is added, the mixture is stirred at room temperature, filtered, concentrated, and stirred after adding n-hexane. The precipitated solid is filtered and dried to obtain a vanadium complex.
3. The preparation method according to claim 2, characterized in that: The following steps are involved: The molar ratio of the pyridinium p-toluenesulfonate, the phenolic compound and 3,4-dihydropyran is 5.6:112:168; The molar ratio of the white powder, n-butyl lithium, diphenylphosphine chloride and R3-MgX is 34:37.4:39:
41.
4. Use of the OP bidentate imine vanadium complex as claimed in claim 1 in catalyzing the copolymerization of ethylene and α-olefins or the homopolymerization of ethylene.
5. The use according to claim 4, characterized in that: In the copolymerization reaction, the OP bidentate imine vanadium complex is used as the main catalyst and the halogenated alkyl aluminum is used as the co-catalyst.
6. The use according to claim 5, characterized in that: The molar ratio of vanadium in the main catalyst to aluminum in the co-catalyst is 1:(5-10000); During the copolymerization reaction, the ethylene pressure is 0.1-10 MPa.
7. Use of the OP bidentate imine vanadium complex as claimed in claim 1 in catalyzing the copolymerization of ethylene and a hydroxyl-containing polar monomer.
8. The use according to claim 7, characterized in that: In the copolymerization reaction, the OP bidentate imine vanadium complex is used as the main catalyst and the halogenated alkyl aluminum is used as the co-catalyst.
9. The use according to claim 8, characterized in that: The molar ratio of vanadium in the main catalyst to aluminum in the co-catalyst is 1:(5-10000); during the copolymerization reaction, the pressure of ethylene is 0.1-10MPa.
Citation Information
Patent Citations
Vanadium complex catalyst containing phenoxy ligand and preparation method and application of vanadium complex catalyst
CN111848669A
Polymerisation and oligomerisation catalysts
CN1761688A